PEMANFAATAN GOOGLE CLASSROOM PADA PEMBELAJARAN DARING TINGKAT SEKOLAH DASAR DIMASA PANDEMI COVID-19 - Arin Nur Fathonah; Heru Purnomo (JURNAL PENDIDIKAN DASAR PERKHASA: Jurnal Penelitian Pendidikan Dasar, 2021)
This research was structured to determine the benefits of technology in learning activities at the elementary school level during the covid-19 pandemic. By using the research method of literature study. The subject or respondent is from the articles that the author uses. In collecting information or data, namely the documentation technique, namely looking for data relating to relevant matters from books, journals, documents. The data analysis technique used by the author is to collect library data, record, process the data. The results of this study are by utilizing the google classroom application, online learning at the elementary school level can be carried out well. This is supported by the features available in the google classroom application, especially the due date feature which can minimize student delays in collecting assignments that the teacher gives.